(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The Profitability of Indian Public Sector Banks A Determinants Study explores the factors affecting 26 Indian Public Sector Banks’ financial results following the global financial crisis. To assess the impact of the macroeconomic and bank-specific factors based on the CAMELS system, the Random Effect Model on the balanced panel data for the period 2012-2017 was carried out. Total Investments in Total Assets, Operating Profit in Total Assets and Provisions on Loans are the banks’ basic factors affecting the profitability of the public sector banks in India, whereas the impact of macroeconomic factors on the profitability of the banks was negligible.